Consequences of players' dismissal in professional soccer: A crisis-related analysis of group-size effects - Bar-Eli, M.; Tenenbaum, G.; Geister, S. (Journal of Sports Sciences, 2006)
This study documents the effect of players' dismissals on team performance in professional soccer. Our aim was to determine whether the punishment meted out for unacceptable player behaviour results in reduced team performance. The official web site of the German Soccer Association was used for coding data from games played in the first Bundesliga between the 1963 - 64 and 2003 - 04 (n = 41) seasons. A sample of 743 games where at least one red card was issued was used to test hypotheses derived from crisis theory (Bar-Eli & Tenenbaum, 1989a). Players' dismissals weaken a sanctioned team in terms of the goals and final score following the punishment. The chances of a sanctioned team scoring or winning were substantially reduced following the sanction. Most cards were issued in the later stages of matches. The statistics pertaining to outcome results as a function of game standing, game location, and time phases - all strongly support the view that teams can be considered conceptually similar to individuals regarding the link between stress and performance. To further develop the concept of team and individual psychological performance crisis in competition, it is recommended that reversal theory (Apter, 1982) and self-monitoring and distraction theories (Baumeister, 1984) be included in the design of future investigations pertaining to choking under pressure.